2022
DOI: 10.3389/fgene.2022.886898
|View full text |Cite
|
Sign up to set email alerts
|

Knockdown of Circ_0037658 Alleviates IL-1β-Induced Osteoarthritis Progression by Serving as a Sponge of miR-665 to Regulate ADAMTS5

Abstract: Background: Osteoarthritis (OA) is a chronic musculoskeletal degeneration disease which brings great pain to patients and a tremendous burden on the world’s medical resources. Previous reports have indicated that circular RNAs (circRNAs) are involved in the pathogenesis of OA. The purpose of this study was to explore the role and mechanism of circ_0037658 in the OA cell model.Methods: The content of interleukin-6 (IL-6) and tumor necrosis factor α (TNF-α) was measured using enzyme-linked immunosorbent assay (E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 53 publications
1
7
0
Order By: Relevance
“…Given the documented ability of IL-1β to induce ADAMTS5 up-regulation in human chondrocytes, , we determined the expression level of IL-1β in Tp-treated hCMEC/D3 cells. After stimulation with Tp at an MOI of 50:1 for 24 h, the expression of IL-1β was detected by RT-qPCR and ELISA.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Given the documented ability of IL-1β to induce ADAMTS5 up-regulation in human chondrocytes, , we determined the expression level of IL-1β in Tp-treated hCMEC/D3 cells. After stimulation with Tp at an MOI of 50:1 for 24 h, the expression of IL-1β was detected by RT-qPCR and ELISA.…”
Section: Resultsmentioning
confidence: 99%
“…Considering that IL-1β had been demonstrated to induce the up-regulation of ADAMTS5 in human chondrocytes, , we also investigated whether Tp regulated the expression of ADAMTS5 through IL-1β. Our findings revealed that Tp induced the production of IL-1β in hCMEC/D3 cells and that recombinant human IL-1β promoted the expression of ADAMTS5 in these cells, which was consistent with previous studies. , Moreover, the inhibition of IL-1β using diacerein significantly reduced the production of ADAMTS5. These data suggested that Tp enhanced ADAMTS5 expression by inducing the production of IL-1β, and IL-1β could regulate the expression of ADAMTS5, which might indirectly affect the subsequent effects of ADAMTS5.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It was shown that miR-665 expression is decreased in the OA chondrocyte model, while overexpression of miR-665 significantly increased chondrocyte proliferation and alleviated chondrocyte inflammation, apoptosis and ECM degradation. 59 The Wnt signaling pathway influences the progression of OA, and miR-665 modulates cell proliferation and apoptosis through its impact on the Wnt/β-Catenin signaling pathway. 60,61 Blocking miR-1972 expression attenuated the production of synovial invasive vascular opacities in RA.…”
Section: Discussionmentioning
confidence: 99%
“…Cells were cultured in DMEM medium (Gibco, Carlsbad, CA, USA) containing 10% FBS (Gibco) at 37℃ with 5% CO 2 . In this, 10 ng/mL IL-1β was used to stimulate CHON-001 cells for 24 h to construct OA cell models [ 24 , 25 ].…”
Section: Methodsmentioning
confidence: 99%